2019
DOI: 10.1111/nep.13507
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis catheter management practices in Australia and New Zealand

Abstract: Aim: Dialysis catheter-associated infections (CAI) are a serious and costly burden on patients and the health-care system. Many approaches to minimizing catheter use and infection prophylaxis are available and the practice patterns in Australia and New Zealand are not known. We aimed to describe dialysis catheter management practices in dialysis units in Australia and New Zealand.Methods: Online survey comprising 52 questions, completed by representatives from dialysis units from both countries.Results: Of 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…(6) Many interventions have been studied with the aim of reducing HD-CRBSI, and the nature of this literature has likely contributed to practice variation. (6)(7)(8)(9) The recent Making Dialysis Safer for Patients Coalition initiative, led by the Centers for Disease Control and Prevention (CDC), is testament to the need for standardized approaches to infection prevention in dialysis services as was the success of the Keystone Michigan Project. (10,11) Herein, we review the research that formed the basis of the design and protocol of the REDUcing the burden of dialysis Catheter ComplicaTIOns -a National approach (REDUCCTION) trial, a stepped-wedge cluster randomized clinical trial of a suite of clinical interventions aimed at reducing the rate of HD-CRBSI across Australian renal services.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Many interventions have been studied with the aim of reducing HD-CRBSI, and the nature of this literature has likely contributed to practice variation. (6)(7)(8)(9) The recent Making Dialysis Safer for Patients Coalition initiative, led by the Centers for Disease Control and Prevention (CDC), is testament to the need for standardized approaches to infection prevention in dialysis services as was the success of the Keystone Michigan Project. (10,11) Herein, we review the research that formed the basis of the design and protocol of the REDUcing the burden of dialysis Catheter ComplicaTIOns -a National approach (REDUCCTION) trial, a stepped-wedge cluster randomized clinical trial of a suite of clinical interventions aimed at reducing the rate of HD-CRBSI across Australian renal services.…”
Section: Introductionmentioning
confidence: 99%
“…This study is important because it identifies that, despite the availability of a range of evidence‐based clinical practice guidelines in relation to insertion, management and removal of dialysis CVC's, considerable variation in clinicians' practice was evident. While this has been identified in other studies, this is the first study to seek clinicians' perceptions about their practices and thus makes an important contribution to knowledge and understanding of challenges clinicians face.…”
Section: Discussionmentioning
confidence: 96%
“…The findings align with other studies that identified inconsistency in dressing practices. 7,22 It is uncertain why these variations in practice exist but it appears to relate to perceived environmental and patient factors rather than evidence. This lack of standardization with attendant variation in practice may be regarded as unsafe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results relating to catheter management have been previously reported. 8 Here, we present the results describing current variation in arteriovenous access management practices in both countries.…”
mentioning
confidence: 99%